Care standards of neonates born with Fetal Alcohol Syndrome (FAS) during hospitalization: project - Pałucka, Klaudia; Pakuła, Justyna; Łepecka-Klusek, Celina; Pilewska-Kozak, Anna B.; Bałanda-Bałdyga, Agnieszka (Nursing in the 21st Century, 2014)
CARE STANDARDS OF NEONATES BORN WITH FETAL ALCOHOL SYNDROME (FAS) DURING HOSPITALIZATION: PROJECT Introduction. Establishing norms for nursing care in the field of neonatal nursingis a very important issue of high-standard nursing care. Demand for higher and better quality of neonatal care as well as continuous improvement is bound with the need to systemize, update and establish standards of everyday nursing/obstetric care of neonates born with fetal alcohol syndrome (FAS). Aim. The article aims at the presentation of a project of standards for nursing care of neonates born with FAS, based on the review of literature and current practice. Conclusion. According to the standards proposed, a neonate born with FAS, either suspected or diagnosed, is to be provided with professional nursing care. Nursing process should account for any actual individual problems a neonate’s birth can pose. Midwife/nurse is to provide adequate care for such neonates, depending on neonate’s health condition and parents’ efficacy. It increases mother’s/father’s motivation to follow recommendations associated with the necessity of further treatment and followup.